Effect of Hydraulic Activity on Crystallization of Precipitated Calcium Carbonate (PCC) for Eco-Friendly Paper - Kim, Jung-Ah (Molecular Diversity Preservation International (MDPI), 2009)
Wt% of aragonite, a CaCO(3) polymorph, increased with higher hydraulic activity (°C) of limestone in precipitated calcium carbonate (PCC) from the lime-soda process (Ca(OH)(2)-NaOH-Na(2)CO(3)). Only calcite, the most stable polymorph, was crystallized at hydraulic activity under 10 °C, whereas aragonite also started to crystallize over 10 °C. The crystallization of PCC is more dependent on the hydraulic activity of limestone than CaO content, a factor commonly used to classify limestone ores according to quality. The results could be effectively applied to the determination of polymorphs in synthetic PCC for eco-friendly paper manufacture.